(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
This study was conducted to determine the prevalence and fertility of Hydatid cysts of Echinococcus granulosus in Cattle slaughtered in selected abattoirs in Northern Nigeria and Federal Capital Territory (FCT) from February to December, 2022. Gross examination was carried out by visual inspection and palpation of lungs and liver of 1,881 Cattle in order to determine the availability and organ localization of hydatid cysts. A total of 95(5.1%) of the study population harboured one or more cysts in liver and lungs. Highest prevalence was recorded in cattle slaughtered in Gombe State (10.9%) followed by Kaduna (6.2%) the least was in Kogi State (1.9%). The difference of prevalence among the states was statistically significant (p<0.05). There was association of prevalence of hydatid cysts with location in Gombe (OR=2.637, 95% CI=1.570-4.431) which was significant and Kaduna states (OR=1.451, 95% CI=0.957-2.200) but not significant. There was no association of hydatid cyst infection with location in cattle slaughtered in FCT, Kogi and Plateau States (OR<1.0).Overall age-specific prevalence of cysts in cattle was directly proportional with age; the 5 years and above age group had highest prevalence (6.2%) while the least was in 1-2 years age group (1.2%). Prevalence was significantly associated only with cattle in 5 years and above age group (OR=2.141, 95% CI=1.295-2.538). Difference in prevalence of hydatid cysts among the age groups in all locations was not statistically significant (p>0.05). Overall prevalence of hydatid cysts was higher in females (5.7%) than males (4.0%) the difference was not statistically significant (p>0.05); ...